The crystallization kinetics and thermal conductivity of alumina/fluorescein sodium salt (Al2O3/FSS) composites - Yakuphanoğlu, Fahrettin; Sekerci, M (Iop Publishing Ltd, 2005)
The thermal conductivity and crystallization mechanism of alumina (Al2O)/fluorescein sodium salt (FSS) composites prepared by the powder metallurgy method have been investigated by means of differential thermal analysis. The Kissinger method is applied to determine the crystallization kinetics from the endotherm peaks. The activation energy E and Avrami parameter n were calculated. The kinetic parameters (E and n) have made it possible to postulate the type of crystal growth exhibited in the crystallization process. The crystallization growth is found to be one-dimensional for the composite system. The thermal conductivity of the composite system was also determined by differential scanning calorimetry.
Keywords: Decomposition; Glass